The antioxidant activity of carotenoid pigments in the bacterial symbionts of seagrass Syringodium isoetifolium - Pringgenies, Delianis; Idris, Riyada (Ma Chung Research Center for Photosynthetic Pigments, 2019)
Carotenoids are pigments of red, yellow and orange which are found in plants, animals and bacteria, and are known to have antioxidant activity. This study aims to identify the carotenoid pigments detected in seagrass Syringodium isoetifolium bacterial symbionts. Isolation of bacteria was conducted using dispersive media Zobell 2116E. Bacterial isolates were cultured and then centrifuged at 8000 rpm for 10 minutes and extracted using methanol. Identification of the pigment was done by using High Performance Liquid Chromatography (HPLC) reversed phase ODS / C18. The mobile phase was carried out using a mixture of methanol: acetonitrile (7: 3 v / v). Free radical reduction activities determined by the method of DPPH (diphenylpicrylhydrazil) and its absorbance was measured at a wavelength of 517 nm. Identification of the bacterial symbionts from the seagrass S. isoetifolium performed using 16S rDNA PCR method. The results showed that, of the 12 bacterial isolates obtained, isolate 7A was proven to contain caratenoid pigment. Pigment extracts of the bacterial isolates had free radical DPPH reduction activity of 40.4%. The results showed that the identification of bacteria isolates 7A had 100% level of kinship with the bacteria Bacillus amyloliquifaciens.